Computational modeling of masonry structures using the discrete element method - Sarhosis, Vasilis 1981-; Bagi, Katalin; Lemos, Jose V.; Milani, Gabriele (Advances in civil and industrial engineering (ACIE) book series, 2016)
This book explores the latest digital solutions for the analysis and modeling of brick, stone, concrete, granite, limestone, and glass block structures, focusing on critical research on mathematical and computational methods for masonry analysis